PELATIHAN CODING ROBOTIK BERBASIS STEM BAGI MAHASISWA PENDIDIKAN FISIKA UNJA PEMBELAJARAN INOVATIF MELALUI PENGALAMAN PRAKTIS (HANDS-ON) - Susanti, Nova; Hamidah, Hamidah; Iriani, Dewi; Aina, Mia; Fitria, Desi (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
Physics Education students, as future science educators, are required to possess 21st-century competencies, including critical thinking, problem-solving, and technological literacy. However, initial observations revealed that most students at Jambi University have not yet gained direct experience in applying coding and robotics as STEM-based learning media, which may hinder their readiness to face the challenges of teaching in the Industrial 4.0 era. This community service program was designed to enhance students’ technological literacy and STEM competencies through hands-on robotic coding training, employing methods such as workshops, tool demonstrations, educational robot programming practice, and project-based reflection. The training was conducted over two days and was attended by 40 students from the Physics Education Study Program at Jambi University. The evaluation results indicated that 85% of participants improved their knowledge and skills in robotic coding, 79% expressed enjoyment in using robotics applications and felt confident in creating new innovations, and 74% stated their interest in continuing to develop robotic applications, reflecting the sustainability of their motivation. Overall, this program successfully strengthened students’ innovative skills and broadened their perspectives on the integration of technology in education, with strong potential for replication to support the STEM curriculum and the Merdeka Belajar policy.